APLIKASI KARBON GRAFIT UNTUK IMOBILISASI ION PB DALAM CAIRAN DENGAN METODE ELEKTROLISIS - Sariasih, Ni Wayan; Suyanto, Hery; Wendri, Nyoman (BULETIN FISIKA; Vol 17 No 2 (2016): BULETIN FISIKA, 2016)
This study aims to determine the lowest concentration of Pb element that can be immobilized by carbon graphite with electrolysis method. Electrolysis used carbon electrodes of graphite as the anode and cathode with current of 52.7 mA. The concentrations of Pb solution used in this research started from of 100 till 0.1 ppm. Pb element deposited on the cathode then irradiated by Nd - YAG laser ( 1064 nm, pulse width 7 ns ) of 100 mJ and its emission intensity of 405.78 nm was captured by the spectrometer HR 2500 +, then the data plotted in intensity as a function of wavelength . The optimum data of charged for the electrolysis process was 80 coulomb and minimum concentration (limit of detection) of Pb that was capable immobilized by carbon graphite was 0,06 ppm.